Power and organisational change: a case study - João Pedro Oliveira (2010)
This thesis reports the results of a case study conducted in a Portuguese manufacturing organization, a part of a large group, which endured profound organizational changes. The initial objective of the research was to explore, in a processual way, the long-term interactions between an Enterprise Resource Planning (ERP) system, the consultants that implemented it and management accounting and control, in this organization. However, during the fieldwork, the researcher was confronted with an apparent puzzle: in the past, formally powerful 'central' actors had been confronted with important limitations - including in their relations with formally less powerful actors, particularly 'local' actors at the plant level. At the time of the fieldwork, however, the situation had substantially changed. The researcher was therefore confronted with a puzzle, which seemed to be about the distribution of power in the organization, about who the powerful actors were and, more fundamentally, what caused (or limited) actors' relational power. (...) This thesis proposes several contributions concerning the repercussions of the collective of innovations across the circuits of power. Some examples are embedding rules in technology (Volkoff et al., 2007) and organizational processes, redefining the scope of agencies, creating non-zero sum outcomes, and the emergence of the perception of control inevitability and naturalness within organizational normalcy. Collectively, these innovations promoted rules enactment (by both human and non-human actors) in ways that benefited the interests of central actors. In addition, this thesis proposes contributions related with the two theoretical frameworks and literatures framing the research. It proposes several refinements to Clegg's (1989) framework, comprising changes in its graphical layout, linkages and even concepts. The second contribution is an ANT-inspired, OIE model of rule-based action. This model draws on Burns and Scapens' (2000) macro structure and concepts, but it is actually a completely new model. It adopts a wide definition of rules, also viewing them as internal structures orienting actors. Thus defined, rules underlie routines and fill a gap in routines-focused frameworks - in particular, when there are no established routines as regards particular issues. The model acknowledges intra-organizational diversity and focuses on the processes of introduction, interpretation, acceptance and enactment of rules. It also relates rules with material conditions, in particular since rules may be technologically and organizationally embedded. Finally, the model highlights that rules may be enacted by both human actors (individual and collective) and non-human actors. The model provides a novel way to conceptualise how actors' interests may be achieved through the various intersections between rules and material conditions, and by the ultimate enactment of rules by both human and non-human actors.